2012
DOI: 10.1136/bmj.e2794
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against pandemic A/H1N1 2009 influenza in pregnancy and risk of fetal death: cohort study in Denmark

Abstract: Objective To investigate whether an adjuvanted pandemic A/H1N1 2009 influenza vaccine in pregnancy was associated with an increased risk of fetal death.Design Nationwide register based cohort study. Setting Denmark.Participants All clinically recognised singleton pregnancies that ended between November 2009 and September 2010. Individual level data on exposure to an inactivated AS03 pandemic A/H1N1 2009 influenza vaccine (Pandemrix) and potential confounders were linked to the study cohort using a unique perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 24 publications
3
98
1
1
Order By: Relevance
“…The C-statistic (an estimate of the ability of the propensity score model to predict vaccination status) was 0.81 for first-trimester exposure and 0.62 for second-or third-trimester exposure. After 1:1 propensity score matching, 660 (330 exposed) infants were included in analyses of adverse fetal outcomes associated with vaccination in the first trimester, and 13 284 (6642 exposed) in analyses of adverse fetal outcomes associated with vaccination in the second or (16) 49 (14) 54 (16) 49 (15) 7472 (16) 727 (11) 751 (11) 727 (11) (21) 68 (21) 72 (22) 8095 (17) 1329 (20) 1321 (20) 1327 (20 (11) 48 (14) 36 (11) 43 (13) 5038 (11) 867 (13) 875 (13) 867 (13) Population density 100-199 inhabitants/km 2 4693 (20) 65 (19) 67 (20) 63 (19) 9573 (21) 1241 (19) 1219 (18) 1241 (19) Population density 50-99 inhabitants/km 2 6074 (27) 78 (23) 72 (22) 77 (23) 12 607 (27) 1596 (24) 1551 (23) 1596 (24) Population density Յ49 inhabitants/km 2 1115 (5) 16 (5) 23 (7) 14 (4) 2336 (5) 277 (4) 264 (4) 277 (4) Place (4) 16 (5) 15 …”
Section: Study Cohortmentioning
confidence: 99%
“…The C-statistic (an estimate of the ability of the propensity score model to predict vaccination status) was 0.81 for first-trimester exposure and 0.62 for second-or third-trimester exposure. After 1:1 propensity score matching, 660 (330 exposed) infants were included in analyses of adverse fetal outcomes associated with vaccination in the first trimester, and 13 284 (6642 exposed) in analyses of adverse fetal outcomes associated with vaccination in the second or (16) 49 (14) 54 (16) 49 (15) 7472 (16) 727 (11) 751 (11) 727 (11) (21) 68 (21) 72 (22) 8095 (17) 1329 (20) 1321 (20) 1327 (20 (11) 48 (14) 36 (11) 43 (13) 5038 (11) 867 (13) 875 (13) 867 (13) Population density 100-199 inhabitants/km 2 4693 (20) 65 (19) 67 (20) 63 (19) 9573 (21) 1241 (19) 1219 (18) 1241 (19) Population density 50-99 inhabitants/km 2 6074 (27) 78 (23) 72 (22) 77 (23) 12 607 (27) 1596 (24) 1551 (23) 1596 (24) Population density Յ49 inhabitants/km 2 1115 (5) 16 (5) 23 (7) 14 (4) 2336 (5) 277 (4) 264 (4) 277 (4) Place (4) 16 (5) 15 …”
Section: Study Cohortmentioning
confidence: 99%
“…None showed an increased risk on adverse pregnancy outcomes. [12][13][14][15][16][17][18][19] The majority of the studies concerned the effect of Pandemrix â , adjuvanted with ASO3. None of the studies included follow up of the offspring up to 1 year of age.…”
mentioning
confidence: 99%
“…In addition, these authors recently reported on the risk of fetal death (spontaneous abortion and stillbirth) in the same cohort and found no increased risk after vaccination in pregnancy. 10 These results suggest that this monovalent adjuvanted pandemic vaccine is safe when given during pregnancy.…”
mentioning
confidence: 93%